Rancangan Modul Peran Keluarga dalam Perawatan Luka pada Pasien Ulkus Diabetikum - Maharani, Sri Astuti; Yayat, Yayat; Rukhayana, Hikmat; Budiman, Budiman; Susilawati, Susilawati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to create a module design for the role of the family in wound care for diabetic ulcer patients. The research method used is qualitative descriptive explorative research utilizing the research and development method. The results of the study showed that the interview results showed that the role of the family in wound care for diabetic ulcer patients had four themes, namely family knowledge about diabetes mellitus, the role of the family in caring for diabetic ulcer patients, the role of the family when they find out that one of their family members has diabetes mellitus and the role of the family in wound care for patients with diabetic ulcers. In conclusion, the study produced a module design for families caring for family members with diabetic ulcers. Keywords: Family Role, Wound Care, Diabetic Ulcers